Revealing the nature of excitons in liquid exfoliated monolayer tungsten disulphide - Kłopotowski, Łukasz; Backes, Claudia; Mitioglu, A. A.; Vega-Mayoral, V.; Hanlon, D.; Coleman, J. N.; Ivanov, V. Y.; Maude, D. K.; Plochocka, P. (Nanotechnology, 2016)
Transition metal dichalcogenides (TMD) hold promise for applications in novel optoelectronic devices. There is therefore a need for materials that can be obtained in large quantities and with well understood optical properties. In this report, we present thorough photoluminescence (PL) investigations of monolayer tungsten disulphide obtained via liquid phase exfoliation. As shown by microscopy studies, the exfoliated nanosheets have dimensions of tens of nanometers and thickness of 2.5 monolayers on average. The monolayer content is about 20%. Our studies show that at low temperature the PL is dominated by excitons localized on nanosheet edges. As a consequence, the PL is strongly sensitive to the environment and exhibits an enhanced splitting in magnetic field. As the temperature is increased, the excitons are thermally excited out of the defect states and the dominant transition is that of the negatively charged exciton. Furthermore, upon excitation with a circularly polarized light, the PL retains a degree of polarization reaching 50% and inherited from the valley polarized photoexcited excitons. The studies of PL dynamics reveal that the PL lifetime is on the order of 10 ps, which is probably limited by non-radiative processes. Our results underline the potential of liquid exfoliated TMD monolayers in large scale optoelectronic devices.
Gesehen am 20.05.2020